Environmental Entrepreneurship markets meet the environment in unexpected Places - Huggins, Laura E. (Northampton Edward Elgar, 2013)
In this innovative book, Laura E. Huggins finds path breaking entrepreneurial solutions to difficult environmental challenges in some of the world's poorest areas.
Includes index
Keywords: Entrepreneurship